THE ESSENCE AND FUNCTIONS OF FINANCE: A COMPREHENSIVE REVIEW AND ANALYSIS - Turayev Alijon Akmal o‘g‘li; Xaydarov O’rinboy (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Finance is a cornerstone of modern economic systems, encompassing the principles, mechanisms, and institutions that govern the management of financial resources, allocation of capital, and mitigation of risk. This paper offers a comprehensive examination of the essence and functions of finance, drawing upon a diverse array of theoretical perspectives, empirical research, and practical insights. We delve into the fundamental concepts underpinning finance, exploring its historical roots, theoretical frameworks, and practical applications within contemporary economies.